TINJAUAN FIQH MUAMALAH TERHADAP PRAKTIK KERJASAMA BANK SAMPAH DI DESA CANDIMULYO KEC. DOLOPO KAB. MADIUN - Roisul Malik (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
In general, a bank is a place where we can do various kinds of transactions such as withdrawal, borrowing, and depositing money. But the object used as a transaction tool here is not something as valuable as money, but garbage. So, people who want to become customers of this bank do not need to have assets or something that is valuable (either money or other valuables), simply by owning trash, then they can become customers. In Islam, this form of cooperation is one form of cooperation in the economic field that is a form of giving assets from one person to another as venture capital where the profits obtained will be divided between the two of them in accordance with the agreement. The purpose of this study was to examine the muamalat contract which was applied by a garbage bank in Madiun Regency. Factual information obtained from Bank Sampah